2013
DOI: 10.1007/s00296-013-2817-x
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural analysis of platelets, erythrocytes, white blood cells, and fibrin network in systemic lupus erythematosus

Abstract: The study suggests that patients with systemic lupus erythematosus (SLE) present with distinct inflammatory ultrastructural changes such as platelets blebbing, generation of platelet-derived microparticles, spontaneous formation of massive fibrin network and fusion of the erythrocytes membranes. Lupoid platelets actively interact with other inflammatory cells, particularly with white blood cells (WBCs), and the massive fibrin network facilitates such an interaction. It is possible that the concerted actions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…It is also well-known that a general hypercoagulable state is present in various inflammatory conditions and we and others have shown changes to RBC (eryptosis) and platelets hyper-activation in various conditions, including type 2 diabetes, Parkinson’s disease, Alzheimer’s disease and rheumatoid arthritis4849505152. In all of these diseases, the 3 cytokines of interest in this paper, feature prominently as major mechanistic role players in the inflammatory profiles of the diseases.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…It is also well-known that a general hypercoagulable state is present in various inflammatory conditions and we and others have shown changes to RBC (eryptosis) and platelets hyper-activation in various conditions, including type 2 diabetes, Parkinson’s disease, Alzheimer’s disease and rheumatoid arthritis4849505152. In all of these diseases, the 3 cytokines of interest in this paper, feature prominently as major mechanistic role players in the inflammatory profiles of the diseases.…”
Section: Resultsmentioning
confidence: 87%
“…In this paper, we include SEM micrographs taken as part of previous published papers, to support the in vitro results presented here4849505152. The inflammatory blood sample preparation was done as discussed for the healthy volunteers and also in the various papers itself.…”
Section: Methodsmentioning
confidence: 83%
“…Although we have observed anomalies in the kinds of fibrin fibres produced in the plasma of patients with various inflammatory diseases (e.g. (Pretorius et al, 2011b;Pretorius et al, 2011c;Pretorius et al, 2012;Pretorius et al, 2013b;Pretorius et al, 2014a;Pretorius et al, 2014b;Kell and Pretorius, 2015b;Pretorius et al, 2015;Kell and Pretorius, 2016a)), this is the first time that we have observed fibrin amyloid in Parkinson's Disease, as assessed by thioflavin T staining and its sensitivity (and that of fibres observed in the SEM) to LBP. While fibrin and αsynuclein can coaggregate (Bhattacharjee and Bhattacharyya, 2014), it is especially notable that the thrombin-dependence and SEM fibre sizes tell us that the fibres we observe imply that they are essentially all made of fibrin.…”
Section: Discussionmentioning
confidence: 57%
“…Upon activation, the platelets release their granular contents and merge with the fibrin fibers. Thus, platelets are seen extremely rarely in healthy whole blood after thrombin addition [12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%